If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 = -1(1 + -6b) -1 = (1 * -1 + -6b * -1) -1 = (-1 + 6b) Add '1' to each side of the equation. -1 + 1 = -1 + 1 + 6b Combine like terms: -1 + 1 = 0 0 = -1 + 1 + 6b Combine like terms: -1 + 1 = 0 0 = 0 + 6b 0 = 6b Solving 0 = 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. 0 + -6b = 6b + -6b Remove the zero: -6b = 6b + -6b Combine like terms: 6b + -6b = 0 -6b = 0 Divide each side by '-6'. b = 0 Simplifying b = 0
| 3n+7=57 | | 6+4X=14+2X | | 20z=-5 | | 20b=-20 | | 9x^2+15-6=18-4x | | 7w+3=8w+3 | | 4+2x-6x=3x | | 42-18=3(x-5) | | -28+15-32z=31 | | 44=11m | | 2x+5-4x=45 | | 20-4x=-8x | | 4x*x=57 | | 800-6m=1000m-10m | | 0.07x=5 | | 3n+1=8n-9 | | 4r^2=12r | | 44c=-44 | | -7a+8(6a-7)=190 | | 5g=g-h | | -4b+24=15b+18 | | a=(-6+9)x(5-12) | | 3x+25=2x+5 | | 5(9-5n)-7=-38 | | 0=-7b-6b | | 4c+2x-5=7x-1 | | 8(4x+5)=136 | | 1-x=17 | | 6+4x-3=43 | | 0.2x+5=19-0.5 | | (4x^5+8x^4-176x^3-72x^2-1260x)=0 | | 10a-4+10=6a+12 |